Colorimetric Sensing of Ascorbic Acid Using Cu-Phen MOFs and Subsequent Digital Image Analysis with Smartphone - M. Lutfi Firdaus; Rizki M. Okumura; Euis Nursaadah; Dewi Handayani; Afrizal Mayub; Lena Rahmidar; Muhamad Diki Permana; Annisa Luthfiah; Santhy Wyantuti; Diana R. Eddy; Yeni Wahyuni Hartati (Science and Technology Indonesia, 2023)
Vitamin C, also known as ascorbic acid, is a crucial nutrient involved in a number of enzymatic processes for tissue healing. Additionally serving as an antioxidant, ascorbic acid is crucial for keeping the immune system strong. It is essential to create a quantitative analytical approach to ascertain ascorbic acid concentration in many samples since its consumption from the daily food should be in the proper quantity. Here, we present a colorimetric probe made of synthetic metal-organic frameworks (MOFs) that changes its color only when samples containing ascorbic acid are present. In this study, phenanthroline served as an organic ligand or linker while copper served as the core metal that formed bonds with it. Cu-Phen MOF color fluctuations at 410 nm (from 408 nm to 412 nm) are linearly related to variations in light absorption. Moreover, as a substitute for spectrophotometry UV-visible, we have created a digital image-based colorimetry. The Cu-Phen MOFs’ color change has the maximum slope and linearity when the blue color intensity is used. The detection limit with high precision of 4.2% under ideal circumstances was 0.1 ppm. The established approach allowed for the exact and accurate assessment of ascorbic acid in genuine samples of star fruit (Averrhoa carambola L.).